Flurlite, Zn3Mn2+Fe3+(PO4)3(OH)2·9H2O, a new mineral from the Hagendorf Süd pegmatite, Bavaria, with a schoonerite-related structure. (2nd January 2018) - Grey, I. E.; Keck, E.; Mumme, W. G.; Pring, A.; Macrae, C. M.; Gable, R. W.; Price, J. R.
Abstract: Flurlite, ideally Zn3 Mn 2+ Fe 3+ (PO4 )3 (OH)2 ·9H2 O, is a new mineral from the Hagendorf-Süd pegmatite, Hagendorf, Oberpfalz, Bavaria, Germany. Flurlite occurs as ultrathin (<1 μm) translucent platelets that form characteristic twisted accordion-like aggregates. The colour varies from bright orange red to dark maroon red. Cleavage is perfect parallel to (001). The mineral occurs on mitridatite and is closely associated with plimerite. Other associated minerals are beraunite, schoonerite, parascholzite, robertsite and altered phosphophyllite. The calculated density of flurlite is 2.84 g cm –3 . It is optically biaxial (–), α = 1.60(1), β= 1.65(1) and γ = 1.68(1), with weak dispersion and parallel extinction, X ≈ c, Y ≈ a, Z ≈ b . Pleochroism is weak, with colours: X = pale yellow, Y = pale orange, Z = orange brown. Electron microprobe analyses (average of seven) with FeO and Fe2 O3 apportioned and H2 O calculated on structural grounds, gave ZnO 25.4, MnO 5.28, MgO 0.52, FeO 7.40, Fe2 O3 10.3, P2 O5 27.2, H2 O 23.1, total 99.2 wt.%. The empirical formula, based on 3 P a.p.f.u. is Zn2.5 Mn 2+ 0.6 Fe 2+ 0.8 Mg0.1 Fe 3+ (PO4 )3 (OH)2 ·9H2 O. Flurlite is monoclinic, P 21 / m, with the unit-cell parameters (at 100 K) of a = 6.3710(13), b = 11.020(2), c = 13.016(3) Å, β = 99.34 (3)°. The strongest lines in the X-ray powder diffraction pattern are [ d obs in Å(I) ( hkl )] 12.900(100)(001); 8.375(10)(011); 6.072(14)(101); 5.567(8)(012); 4.297(21)(003); 2.763(35)(040). Flurlite ( R 1 = 0.057 for 995 F > 4σ( F )) has a heteropolyhedral layer structure, with layers parallel to (001) and with water molecules packing between the layers. The slab-like layers contain two types of polyhedral chains running parallel to [100]: ( a ) chains of edge-sharing octahedra containing predominantly Zn and ( b ) chains in which Fe 3+ -centred octahedra share their apices with dimers comprising Zn-centred trigonal bipyramids sharing an edge with PO4 tetrahedra. The two types of chains are interconnected by corner-sharing along [010]. A second type of PO4 tetrahedron connects the chains to MnO2 (H2 O)4 octahedra along [010] to complete the structure of the (001) slabs. Flurlite has the same stoichiometry as schoonerite, but with dominant Zn rather than Fe 2+ in the edge-shared chains. Schoonerite has a similar heteropolyhedral layer structure with the same layer dimensions 6.4 × 11.1 Å. The different symmetry (orthorhombic, Pmab ) for schoonerite reflects a different topology of the layers.